Respuesta :
Answer:
(x + 9, y - 12 )
Step-by-step explanation:
Given
A(7, 3 ) → A'(16, - 9 )
The change in x is 16 - 7 = 9, the change in y is - -9 - 3 = - 12
Thus the translation rule is
(x, y ) → (x + 9, y - 12 )
Using it's concepts, it is found that the translation rule is given by:
(x,y) →(x+9,y-12)
What is a translation?
A translation is represented by a change in the function graph, according to operations such as multiplication or sum/subtraction in it's definition.
In this problem, Point A(7,3) is translated to A (16,-9), hence the transformations are as follows.
- 7 is added to x.
- 12 is subtracted from y.
Thus, the rule is:
(x,y) →(x+9,y-12)
More can be learned about translation concepts at https://brainly.com/question/4521517